2001
DOI: 10.1177/004728750103900302
|View full text |Cite
|
Sign up to set email alerts
|

Toronto’s Image As a Destination: A Comparative Importance-Satisfaction Analysis by Origin of Visitor

Abstract: The purposes of this study were to examine Toronto visitors’ perceptions of products and services in terms of importance and satisfaction by visitor origin and to apply the results to the importance-satisfaction model to identify strengths in service. The sample consisted of 359 visitors to Toronto in either August or November 1998. The results suggest that, in general, the overall visitors’ image of Toronto is similar. Closer analysis of the visitors’ country of origin, however, shows that there are some impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
124
0
8

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(135 citation statements)
references
References 26 publications
3
124
0
8
Order By: Relevance
“…The authors used this method to measure the cognitive perceptions of New Zealand visitors. Joppe et al (2001) used IPA to examine the image of Toronto and found strengths of the destination and gaps in its marketing strategy.…”
Section: Literature Review Destination Imagementioning
confidence: 99%
“…The authors used this method to measure the cognitive perceptions of New Zealand visitors. Joppe et al (2001) used IPA to examine the image of Toronto and found strengths of the destination and gaps in its marketing strategy.…”
Section: Literature Review Destination Imagementioning
confidence: 99%
“…Otros autores señalan el concepto de "valor percibido" (perceived value) a la hora de referirse a la evaluación realizada por un cliente a partir de la comparación entre las ventajas que puede obtener de un producto o servicio (en este caso de la visita a un destino turístico) y los costes o sacrificios (económicos y no económicos) que conlleva esta (Forgas-Coll et al 2012). Joppe et al (2001) señalan que la búsqueda de una mayor calidad en el sector turístico requiere el desarrollo de formas más específicas para medir la calidad de los servicios, existiendo importantes diferencias en la ratio de satisfacción según el origen de los visitantes, aunque podrían añadirse otros atributos como la motivación de estos. Desde esta perspectiva, es fundamental determinar las diferentes motivaciones para visitar un lugar vinculado al patrimonio cultural inmaterial en el espacio andino, como es el caso de estudio de Cuenca, analizado a continuación en su vinculación con el sombrero de paja toquilla.…”
Section: Satisfacción Del Turistaunclassified
“…IPA has been widely used in various service industries for the purpose of measuring the quality of service encounters. This technique is popular among tourism and hospitality researchers and has been applied to a variety of research settings in the tourism context (Chu & Choi, 2000;Hemmasi, Strong, & Taylor, 1994;Joppe, Martin, & Waalen, 2001;Oh, 2001). In this study, the Importance-Satisfaction Analysis (ISA) is revised from the IPA.…”
Section: Importance-satisfaction Analysis (Isa)mentioning
confidence: 99%